Task lists as infrastructure: an empirical study of multi-project work. (1st January 2012) - Karrbom Gustavsson, Tina; Jerbrant, Anna
Multi-project work is fragmented and unpredictable making project professionals continuously facing the risk of experienced control being reduced. In such work settings, there is an increased need for (temporary) sense making structures. In this article, the concept of infrastructure (Bowker and Star, 2002) is applied to multi-project work. The findings, which are based on 43 interviews with multi-project professionals, reveals that task lists are important infrastructures created for supporting sense making, control and prioritising. The task lists reduces ambiguity and uncertainty and thus bridge the gap between organisational demands and individual resources providing room for improvised action.